A Single LC-MS/MS Analysis to Quantify CoA Biosynthetic Intermediates and Short-Chain Acyl CoAs - Anthony E. Jones; Nataly J. Arias; Aracely Acevedo; Srinivasa T. Reddy; Ajit S. Divakaruni; David Meriwether (Metabolites, 2021)
Coenzyme A (CoA) is an essential cofactor for dozens of reactions in intermediary metabolism. Dysregulation of CoA synthesis or acyl CoA metabolism can result in metabolic or neurodegenerative disease. Although several methods use liquid chromatography coupled with mass spectrometry/mass spectrometry (LC-MS/MS) to quantify acyl CoA levels in biological samples, few allow for simultaneous measurement of intermediates in the CoA biosynthetic pathway. Here we describe a simple sample preparation and LC-MS/MS method that can measure both short-chain acyl CoAs and biosynthetic precursors of CoA. The method does not require use of a solid phase extraction column during sample preparation and exhibits high sensitivity, precision, and accuracy. It reproduces expected changes from known effectors of cellular CoA homeostasis and helps clarify the mechanism by which excess concentrations of etomoxir reduce intracellular CoA levels.